2000
DOI: 10.1097/00004647-200003000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Synaptic Neurotransmission with in Vivo Binding Competition Techniques: A Critical Review

Abstract: Summary: Several groups have provided evidence that posi tron emission tomography (PET) and single-photon emission computed tomography (SPECT) neuroreceptor imaging tech niques might be applied to measure acute t1uctuations in do pamine (OA) synaptic concentration in the living human brain. Competition between OA and radioligands for binding to O2 receptor is the principle underlying this approach. This new application of neuroreceptor imaging provides a dynamic mea surement of neurotransmission that is likely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
761
2
14

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 915 publications
(795 citation statements)
references
References 181 publications
18
761
2
14
Order By: Relevance
“…The reason for this apparent discrepancy is that the DAT are effective at preventing the diffusion of synaptic DA to the extracellular space (Tsukada et al, 2000). Thus, [ 11 C]raclopride imaging provides a more direct measure of D 2 receptor stimulation by DA than microdialysis (see, for further discussion, Laruelle, 2000). In addition, this method is noninvasive, and similar experiments can be conducted in animals and humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this apparent discrepancy is that the DAT are effective at preventing the diffusion of synaptic DA to the extracellular space (Tsukada et al, 2000). Thus, [ 11 C]raclopride imaging provides a more direct measure of D 2 receptor stimulation by DA than microdialysis (see, for further discussion, Laruelle, 2000). In addition, this method is noninvasive, and similar experiments can be conducted in animals and humans.…”
Section: Discussionmentioning
confidence: 99%
“…It should however be pointed out that the duration of the effect of amphetamine on [ 11 C]raclopride or [ 123 I]IBZM V 3 00 exceeds the duration of the increase in extracellular DA (Laruelle et al, 1997). This observation suggests that mechanisms other than simple binding competition, such as DA-induced receptor internalization, are involved in this response (see, for further discussion, Laruelle, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, competition of the various drugs with dopamine for the high-affinity state can be a significant issue. It has been suggested that 20% of the D-2 receptors are occupied by dopamine and 30% of the receptor sites are vulnerable to increases in dopamine (Laruelle 2000).…”
Section: Can Endogenous Dopamine Affect D-2 Occupancy By Clozapine?mentioning
confidence: 99%
“…Several radiotracers for both the excitatory D1-like receptors (D1/D5) and the inhibitory D2-like receptors (D2/D3/D4) have been tested for sensitivity to endogenous dopamine in animals or humans using 11 C or 18 F-labeled compounds. The substituted benzamide derivative [ 11 C]raclopride has consistently been shown to display changes in binding which are consistent with dopamine competition 3 . More recently, antagonist radiotracers with higher D2 receptor affinity compared to raclopride, such as [ 11 C]FLB457 and [ 18 F]fallypride, have been used to investigate extrastriatal brain regions, where the density of D2 receptor is much lower than in the striatum.…”
Section: Pet Radiotracers That Have Enabled Imaging Of Neurotransmmentioning
confidence: 67%